1995
DOI: 10.1103/physreve.52.3923
|View full text |Cite|
|
Sign up to set email alerts
|

Supersaturated electrolyte solutions: Theory and experiment

Abstract: Highly supersaturated electrolyte solutions can be prepared and studied employing an electrodynamic levitator trap (ELT) technique. The ELT technique involves containerless suspension of a microdroplet thus eliminating dust, dirt, and container walls which normally cause heterogeneous nucleation. This allows very high supersaturations to be achieved. A theoretical study of the experimental results obtained for the water activity in microdroplets of various electrolyte solutions is based on the development of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 9 publications
1
21
0
Order By: Relevance
“…[2][3][4][5][6][7][8] There is rapid development in the science of the phase transitions of atmospheric chemistry as well as a growing recognition of the importance of the condensed phase for diverse atmospheric problems. Laboratory work on cirrus and PSC cloud formation at low temperatures and salt crystallization at low relative humidities include 8 publications in 1999, 9-16 19 in 1997-1998, 17-35 14 in 1995-1996, [36][37][38][39][40][41][42][43][44][45][46][47][48][49] 18 in 1993-1994, 50-66 and 18 between 1977 and 1993. [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] Earlier work on salt crystallization is found in refs 85-88. In addition, there have been numerous papers describing field and modeling studies.…”
Section: B Subject Materialsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] There is rapid development in the science of the phase transitions of atmospheric chemistry as well as a growing recognition of the importance of the condensed phase for diverse atmospheric problems. Laboratory work on cirrus and PSC cloud formation at low temperatures and salt crystallization at low relative humidities include 8 publications in 1999, 9-16 19 in 1997-1998, 17-35 14 in 1995-1996, [36][37][38][39][40][41][42][43][44][45][46][47][48][49] 18 in 1993-1994, 50-66 and 18 between 1977 and 1993. [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] Earlier work on salt crystallization is found in refs 85-88. In addition, there have been numerous papers describing field and modeling studies.…”
Section: B Subject Materialsmentioning
confidence: 99%
“…The properties of supersaturated solutions have been studied by the measurement of solubility, density, viscosity, refractive index, diffusivity, and activity. Diffusivity studies [8][9][10][11], spectroscopic studies [12,13], concentration gradients in long vertical columns [4][5][6], and electrodynamic levitation experiments [14,15] have indirectly shown the existence of clusters. The cluster sizes have been estimated for the various systems studied using the diffusivity data by A.S.Myerson et al From the studies we see that NaCl and KCl exist mainly as a monomer in solution, glycine exists mainly as a dimer and urea as an oligomer.…”
Section: Introductionmentioning
confidence: 99%
“…19 Fewer studies have been reported on NaBr. Myerson et al 20 This work reports a study of the hygroscopic properties of NaBr aqueous aerosols by infrared absorption spectroscopy in an aerosol flow cell. The aim is to analyze the detailed behavior of particles as a function of the relative humidity, to understand particle water content as humidity varies.…”
Section: Introductionmentioning
confidence: 96%